Policies and Processes for Social Inclusion: Using EquiFrame and EquIPP for Policy Dialogue: Comment on "Are Sexual and Reproductive Health Policies Designed for All? Vulnerable Groups in Policy Documents of Four European Countries and Their Involvement in Policy Development" - MacLachlan, Malcolm (Int J Health Policy Manag, 2015)
The application of EquiFrame in the analysis of sexual and reproductive health policies by Ivanova et al to a new thematic area, their selection of only some of the Core Concepts of human rights in health service provision and the addition of new vulnerable groups relevant to the purpose of their analysis, are all very welcome developments. We also applaud their application of EquiFrame to policies in countries where it has not previously been used, along with their use of interviews with policy-makers to produce a deeper understanding of policy processes. We argue that clear justification for the inclusion of additional, or replacement of some exiting vulnerable groups within EquiFrame should be accompanied by clear definitions of such groups, along with the evidence-base that justifies their classification as a vulnerable or marginalised group. To illustrate the versatility of EquiFrame, we summarise a range of ways in which it has been used across a number of regions; including a brief Case Study of its use to develop the National Health Policy of Malawi. While EquiFrame focuses on policy content, we preview a new policy analysis tool – Equity and Inclusion in Policy Processes (EquIPP) – which assesses the extent of equity and inclusion in broader policy processes. Together, EquiFrame and EquIPP can be used to help governments and civil society ensure that policies are addressing the much stronger emphasis on social inclusion, now apparent in the Sustainable Development Goals (SDGs).